Integrated Continuous Process Design for Crystallisation, Spherical Agglomeration, and Filtration of Lovastatin - Cameron J. Brown; John McGinty; Muhammad T. Islam; Nazer Rajoub; Omid Arjmandi-Tash; Sara Ottoboni; Muhid Shahid; Stephanie J. Urwin; Ye Seol Lee; Magdalene W. S. Chong; Foteini Papathanasiou; Aruna S. Prakash; et al. (Journal of Pharmaceutical Innovation, 2024)
Purpose This work seeks to improve the particle processability of needle-like lovastatin crystals and develop a small-footprint continuous MicroFactory for its production. Methods General conditions for optimal spherical agglomeration of lovastatin crystals and subsequent product isolation are developed, first as batch processes, and then transferred to continuous MicroFactory operation. Results Methyl isobutyl ketone is a suitable bridging liquid for the spherical agglomeration of lovastatin. Practical challenges including coupling unit operations and solvent systems; mismatched flow rates and inconsistent suspension solid loading were resolved. The successful continuous production of lovastatin spherical agglomerates (D 50 = 336 µm) was achieved. Spherical agglomeration increased the density of the bulk lovastatin powder and improved product flowability from poor to good, whilst maintaining lovastatin tablet performance. Conclusion A continuous, integrated MicroFactory for the crystallisation, spherical agglomeration, and filtration of lovastatin is presented with improved product particle processability. Up to 16,800 doses of lovastatin (60 mg) can be produced per day using a footprint of 23 m 2 .

Assessing household fine particulate matter (PM2.5) through measurement and modeling in the Bangladesh cook stove pregnancy cohort study (CSPCS) - Md Mostafijur Rahman; Meredith Franklin; Nusrat Jabin; Tasnia Ishaque Sharna; Noshin Nower; Tanya L. Alderete; Alaa Mhawish; Anisuddin Ahmed; M.A. Quaiyum; Muhammad T. Salam; Talat Islam (Environmental Pollution, 2023)

Citrinin as a potential anti-cancer therapy: A comprehensive review - Ag-Anne P.M. de Menezes; Raí P.S. Aguiar; José V.O. Santos; Chandan Sarkar; Muhammad T. Islam; Antonio L. Braga; Mohammad M. Hasan; Felipe C.C. da Silva; Javad Sharifi-Rad; Abhijit Dey; Daniela Calina; Ana A.C. Melo-Cavalcante; et al. (Chemico-Biological Interactions, 2023)

Phenotypic and Genotypic Analysis of the Population of Phytophthora infestans in Bangladesh Between 2014 and 2019 - Md. Huzzatul Islam; Sangee Sarkar Shanta; Muhammad Iqbal Hossain; Muhammed Ali Hossain; Md. Monower Hossain; Ebna Habib Md. Shofiur Rahaman; Abdullah Al Mahmud; Md. Abdullah Yousuf Akhond; Louise Sullivan; David E. L. Cooke; Geert J. T. Kessel; Louise R. Cooke; et al. (Potato Research, 2023)
In Bangladesh, the third largest producer of potatoes in Asia, late blight, caused by Phytophthora infestans , is the major constraint to production. Nevertheless, there is a lack of published information on the pathogen population. A collection of 69 isolates obtained from samples of infected potato foliage collected in 2018–2019 varied significantly in their aggressiveness to detached potato leaflets and tuber slices of cv. Diamant. On leaflets, most isolates were highly aggressive, colonizing more than half the surface in 7 days. On tuber slices, while some isolates were highly aggressive, those collected in 2019 were less so. There was a significant effect of the locations from which the isolates were obtained on aggressiveness to both leaflets and tuber slices, but aggressiveness to leaflets and to tuber slices was not significantly correlated. All isolates were A2 mating type and either intermediate (38%) or resistant (62%) in sensitivity to the fungicide metalaxyl . A subset of 24 isolates all had mitochondrial DNA haplotype Ia. Samples of P. infestans DNA (124) from infected potato foliage obtained from Bangladesh (2014–2019) were genotyped by 12-plex SSR. The vast majority (95%) were assigned to EU_13_A2, which was present in every year in which samples were collected. Numerous EU_13_A2 variants were identified, many specific to Bangladesh. Six samples (from 2017 to 2019) had genotypes distinct from EU_13_A2 and with no close match to known European lineages. It is concluded that the current P. infestans population of Bangladesh is dominated by the aggressive lineage EU_13_A2, also dominant in India and Pakistan. The implications of this for control of late blight are discussed.

Novel Controlled Release Polymer-Lipid Formulations Processed by Hot Melt Extrusion - Mohammed Maniruzzaman; Muhammad T. Islam; Sheelagh Halsey; Devyani Amin; Dennis Douroumis (AAPS PharmSciTech, 2016)

Development of sustained-release formulations processed by hot-melt extrusion by using a quality-by-design approach - Muhammad T. Islam; Mohammed Maniruzzaman; Sheelagh A. Halsey; Babur Z. Chowdhry; Dennis Douroumis (Drug Delivery and Translational Research, 2014)